Blowing the Whistle - José Apesteguia; Martin Dufwenberg; Reinhard Selten (University of Bonn, Bonn Graduate School of Economics (BGSE), 2003)
Leniency clauses, offering cartelists legal immunity if they blow the whistle on each other, is a recent anti-trust innovation. The authorities wish to thwart cartels and promote competition. This effect is not evident, however; whistle-blowing may enforce trust and collusion by providing a tool for cartelists to punish each other. We examine the impact of leniency law, and other rules, theoretically and experimentally.
Keywords: L13; D43; C92; 330; Anti-trust; leniency; immunity; amnesty; blow the whistle; cartels; pricecompetition; Bertrand model; experiment; communication; Wettbewerbspolitik; Kartellverfahren; Straffreiheit; Preiswettbewerb; Experiment